Invasive Streptococcus pyogenes Infections in <3-Month-Old Infants in France: Clinical and Laboratory Features - Germont, Zoé; Bidet, Philippe; Plainvert, Céline; Bonacorsi, Stéphane; Poyart, Claire; Biran, Valérie; Frérot, Alice; Faye, Albert; Basmaci, Romain (Frontiers in Pediatrics, 2020)
Few data are available on invasive Group A Streptococcus infections (IGASI) in infants. We described initial clinical and laboratory features and outcomes of <3-month-old infants hospitalized for an IGASI between 2007 and 2016 in France. Patients were identified from the French National Reference Centre for streptococci. IGASI was defined by the isolation of GAS from blood cultures or from other usually sterile sites. Data collection was performed by assessing the patients’ hospitalization reports. Twenty-six patients (15 males; 57.7%) were included. Among 19 cases with available data, 14 (73.7%) were household contacts of a GAS infection, reaching 8/9 (88.9%) in neonates. The diagnoses were bacteremia (n=1918; 73.169.2%); pleural effusion or pneumonia (n=56; 19.223.1%); meningitis with brain abscess (n=1; 3.8%); and septic arthritis (n=1; 3.8%). Fever (n=10; 38.5%), hemodynamic disorders (n=11; 42.3%), respiratory disorders (n=7; 26.9%), thrombocytopenia (n=7; 26.9%), and neutropenia (n=5; 19.2%) were frequently observed. The main emm-genotype was emm-1 (n=8; 30.8%). Thirteen (50.0%) infants have been admitted to intensive care unit, and 2 (7.7%) died. Respiratory disorders, a high C-reactive protein >132 mg/Llevel and the need for transfusion were significantly associated with severity. IGASI remains uncommon in <3-month-old children but leads to a high morbidity. Whether Aan antibiotic prophylaxis for contact neonates of a patient with GAS infection should be considereddecreases the risk of infection remains to be determined.